How many stars in the sky? - Hort, Lenny; Ransome, James (New York, NY : Scholastic Inc., 1991)
One night when Mama is away, Daddy and child seek a good place to count the stars in the night sky.
G3
Keywords: Stars -- Fiction; Night -- Fiction; Father and child -- Fiction; African Americans -- Fiction